2021
DOI: 10.1016/j.aninu.2021.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Dietary high protein-induced diarrhea and intestinal inflammation by activation of NF-κB signaling in piglets

Abstract: The present study aimed to investigate whether inflammation-associated responses in piglets are induced by high protein (HP) through activating nuclear factor kappa B (NF-κB) signaling. Sixteen piglets (35 d of age, Duroc × [Landrace × Yorkshire], weaned at d 21, initial BW = 9.70 ± 0.11 kg) were allocated to 18% and 26% CP (HP group) at random, comprising 8 replicate pens per treatment. The piglets were slaughtered to collect intestinal tissues when apparent, persistent, and stable diarrhea syndromes happened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
(56 reference statements)
0
9
0
Order By: Relevance
“…Small intestinal morphology indices, such as VH, CD, and VH to CD ratio, are generally used as indicators of piglet intestinal absorption and digestion ability ( 25 ). Research has shown that a diet consisting of 26% CP decreased the VH to CD ratio and ileal VH in weaned piglets compared to the 18% CP diet ( 8 ). In another study, dietary reduction of dietary CP levels from 16 to 10% significantly decreased the intestinal VH to CD ratio ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small intestinal morphology indices, such as VH, CD, and VH to CD ratio, are generally used as indicators of piglet intestinal absorption and digestion ability ( 25 ). Research has shown that a diet consisting of 26% CP decreased the VH to CD ratio and ileal VH in weaned piglets compared to the 18% CP diet ( 8 ). In another study, dietary reduction of dietary CP levels from 16 to 10% significantly decreased the intestinal VH to CD ratio ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Yin et al. ( 8 ) also indicated that dietary HP may cause diarrhea in piglets by inducing intestinal inflammation through the activation of the NF-κB signaling pathway. Our previous study found that increasing levels of dietary CP quadratically decreased the feed to body weight gain (F/G) during the 5−10 kg growth stage, while the average daily gain (ADG) during the 10−20 kg growth stage and average daily feed intake (ADFI) and ADG during the 20−30 kg growth stage were quadratically increased ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…The parameters for thermal cycling were set in accordance with our published study [ 21 ]. Primers of Nrf2, SOD, GPX, CAT, Keap-1, TLR4, NF-κB, IL-1β, IL-6, IL-8, IL-10, TNF-α, mucin-2, zonula occludens (ZO) -1, ZO-2, occludin, claudin-1, claudin-1 and glyceraldehyde-3 phosphate dehydrogenase (GAPDH) were obtained from other reports [ 19 , 22 , 23 , 24 , 25 ] and are listed showed in Table S2 . All primers were commercially synthesized by Sangon Biotech Co., Ltd. (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…This is supported by shallower crypt depth (CD) which facilitates the proliferation of intestinal epithelial cells to further improve absorption from the SI. Thus, both VH and CD, and the ratio of VH/CD (known as V/C) are often used to evaluate intestinal absorptive capacity [ 73 ]. Furthermore, intestinal microbes can ferment indigestible substrates such as dietary fiber and endogenous intestinal mucus to produce short-chain fatty acids (SCFA) which are easily absorbed [ 74 ].…”
Section: Mechanism Of Is On Growth Performance Of Livestock and Poultrymentioning
confidence: 99%